Effects Of Multimedia Induced Emotions On Achievement Intrinsic Motivation And Satisfaction Among Polytechnic Students With Different Levels Of Emotional Intelligence - David Pandya Kumar, Jeya Amantha (2016)
The field of research is similar with studies in the area of emotional design in multimedia learning. The purpose of this study was to highlight the effects of induced emotions through multimedia elements and how personality traits effects multimedia learning cognitively and affectively. Therefore, three types of coursewares were designed and developed to either induce positive (PosD), neutral (NeuD) or negative (NegO) emotions based on the aesthetic value of colours, fonts and images. This method of redesigning essential multimedia elements to induce emotions for a positive outcome is defined as emotional design in multimedia learning.